The End of Burnout : why work drains us and how to build better lives - Malesic, Jonathan, ....- (Oakland : University of California Press, 2022)
Burnout has become our go-to term for talking about the pressure and dissatisfaction we experience at work. But in the absence of understanding what burnout means, the discourse often does little to help workers who suffer from exhaustion and despair. Jonathan Malesic was a burned out worker who escaped by quitting his job as a tenured professor. In The End of Burnout, he dives into the history and psychology of burnout, traces the origin of the high ideals we bring to our jobs, and profiles the individuals and communities who are already resisting our cultural commitment to constant work.
Keywords: Burn-out.